Business process automation with ProcessMaker 3.1 : a beginner's guide - Majekodunmi, Dipo (Apress, 2018)
Use this practical, hands-on guide to get started with ProcessMaker. The book provides clear steps for you to walk through and set up ProcessMaker on your own system and make processes run faster and smarter. You will model and build a complete business process for requesting, approving, and reporting expenses. In the course of building the process, you will understand: The Workflow Designer for modeling business processes using BPMN 2.0 The Dynaform Designer for creating responsive HTML forms Input and Output documents for capturing supporting documents for business processes and generating standardized documents from the data captured in a process Triggers for implementing custom business logic and extending ProcessMaker functionality What You?ll Learn: Send email notifications and add comments to cases Build complex routing rules Manage users and their permissions Deploy ProcessMaker to a cloud server Configure and use the ProcessMaker mobile app.